Exposure-adjusted incidence rates and severity of competition injuries in Australian amateur taekwondo athletes: a 2-year prospective study - Lystad, R. P.; Graham, P. L.; Poulos, R. G. (British Journal of Sports Medicine, 2013)
Background/aim The main purposes of this study were to determine the injury incidence and severity in Australian amateur taekwondo athletes, and to investigate potential risk factors for injury in competition taekwondo. Methods Data were collected at New South Wales State Championships in 2010 and 2011. Injuries were diagnosed by onsite sports medicine personnel and the actual number of days lost from full participation was used to determine injury severity. Injury incidence rates were calculated per 1000 athlete-exposures (injury incidence rate (IIRAE)) and per 1000 min of exposure (IIRME) and presented with 95% CI. Results The overall IIRAE and IIRME were 59.93 (95% CI 51.16 to 69.77) and 16.32 (95% CI 13.93 to 19.00), respectively. Children under 10 years had significantly lower IIRAE compared with older age groups and black belts had significantly higher IIRAE compared with yellow belts, however, after accounting for the exposure time it was revealed that 10-year-olds to 14-year-olds and red belts incurred higher IIRME. This study highlights the importance of including IIRs that account for exposure-time. In contrast with previous estimates, the current data indicated that one-third of injuries were moderate to severe. Relative to other body regions the upper limb had a higher proportion of moderate-to-severe injuries, and compared with the lower limb there was a disproportionate number of upper limb injuries resulting in fractures. Conclusions The findings suggest that the impact of injury on taekwondo athletes is significant, and should serve as an impetus to stakeholders to develop and implement injury prevention activities within the sport.